ANALISIS PENDEKATAN TRANSDISIPLINER HADIS ‘’KULLU MUSKIRIN HARAM’’ (KAJIAN SANAD DAN MATAN) - Sinaga, M. Hendri Sugara (UIN Sumatera Utara Medan, 2021)
Intoxicating substances cintinue to have derivative products, raning from liquids, solids, powders and even gases. This shows that, the use of intoxicating substances continues to have users who continue to graw with time and age. Even though it is said to be an intoxicating sunstance continue to exist, both at home and abroad. This research is included in the type of manuscript study research. This thesis was carried out using a qualitative method by collecting data and then discussing it in depth withreference to the syarah hadith supported by other relevant references related to drugs. Data collection techniques in this study used the tahrij al-hadith and i’tibar sanad methods.the finding in this thesis is more than one hadith one which indirectly explains drug law, which is called muskir (anything that intoxicates). The hope throuhg this thesis is the understanding of drug law is not understood textually so that it can produce broader legal products and can avoid drug uses because this thesis is also studied from a transdisciplinary perspective of hadith, which not only produces laws but also explains the negative impacts of drugs in the healt, economic and social fields. The results of this study indicate that the hadiths that explain the prohibion of muskir (anyhing that intixicates) have a number of wwll-known and quality hadiths that are authentic. For the university and can be a source of refence further research.